Species origin of exogenous transcription factors affects the activation of endogenous pluripotency markers and signaling pathways of porcine induced pluripotent stem cells - Zhou, Meng; Zhang, Manling; Guo, Tianxu; Zhao, Lihua; Guo, Xiyun; Yin, Zhibao; Cheng, Linxin; Liu, Han; Zhao, Lixia; Li, Xihe; Li, Rongfeng (Frontiers in Cell and Developmental Biology, 2023)
The incomplete silencing of exogenous transcription factors (TFs) and the lack of endogenous counterpart activation hampers the application of porcine induced pluripotent stem cells (piPSCs). We used porcine, bovine and murine TFs to reprogram porcine fetal fibroblasts. Porcine TFs-derived piPSCs (ppiPSCs) showed the highest levels of endogenous pluripotency markers activation, were able to differentiate into three germ layers and primordial germ cell-like cells (PGCLCs) and integrated into neural ectoderm of E7.5 mouse embryos in vitro. The bovine TFs derived piPSCs (bpiPSCs) expressed endogenous pluripotency markers higher than murine TFs derived piPSCs (mpiPSCs), but both had limited differentiation ability in vitro and depended on continuous expression of exogenous TFs for the maintenance. RNA sequencing confirmed ppiPSCs had distinct global transcriptional profiling, upregulated Hippo, PI3K-Akt, MAPK and relevant pluripotency signaling pathways as porcine blastocyst inner cell mass and expressed PGC early related genes. In addition, a positive and a negative correlation between exogenous and endogenous TFs’ expression level were observed in ppiPSCs and bpiPSCs lines, respectively. The TFs’ protein structures in pig were more similar to cattle than to mouse. In conclusion, the species affinity of the exogenous TFs is a key element, and the own species origin of TFs is optimal for iPSCs generation and application.